2014
DOI: 10.1177/1524838014557288
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Survivors of Child Sexual Abuse

Abstract: Preventive and clinical interventions for survivors of CSA should utilize psychoeducation and cognitive strategies that are adapted to the developmental level of the victim and that seek to enhance social support from significant others. Future research should focus on longitudinal research designs considering resilience rather as a dynamic process with multiple dimensions in a social and developmental context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(109 citation statements)
references
References 78 publications
2
84
0
11
Order By: Relevance
“…Stress has been considered as a risk factor (Thoits, 2010). Self-efficacy, resilience, and social support seeking have been considered as protective factors (Bensimon, 2012;Daniels et al, 2013;Domhardt, Münzer, Fegert, & Goldbeck, 2015;Lee et al, 2013;Sabina & Banyard, 2015). Avoidance has been considered as maladjustment (Eskin et al, 2013).…”
Section: Hypothesesmentioning
confidence: 99%
“…Stress has been considered as a risk factor (Thoits, 2010). Self-efficacy, resilience, and social support seeking have been considered as protective factors (Bensimon, 2012;Daniels et al, 2013;Domhardt, Münzer, Fegert, & Goldbeck, 2015;Lee et al, 2013;Sabina & Banyard, 2015). Avoidance has been considered as maladjustment (Eskin et al, 2013).…”
Section: Hypothesesmentioning
confidence: 99%
“…Adaptive functioning with regards to mental health is also evident in sexually abused or assaulted children and adolescents (Daigneault et al 2007a;Hébert et al 2014;Domhardt et al 2014), which has prompted research on identifying protective factors associated with resilience or adaptive functioning (Marriott et al 2014;McClure et al 2008;Spaccarelli and Kim 1995).…”
Section: Introductionmentioning
confidence: 99%
“…16,17,22,30 Through this process, we identified five studies; saturation was reached when no new studies were identified. 49 We conducted a broad Google search on sexual violence and/or resilience and identified organisations locally and internationally that conducted related research.…”
Section: Select Studiesmentioning
confidence: 99%
“…This burgeoning interest has also resulted in a limited number of reviews. 16,17,22 None of these reviews has, however, focused specifically on resilience processes in adolescent girls who have survived CSA. The reviews by Domhardt et al 17 and Marriot et al 16 included men and women of all ages, whilst Lekganya's 22 systematic review focused on studies with adult women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation